95.8k views
2 votes
Find f(-7) if f(x) = 2x + 8. -6 2 3 22

User Lepix
by
4.6k points

1 Answer

6 votes
2x+8 is the same as 2*x+8. This is basically saying "multiply 2 times some number, then add on 8". The order of operation PEMDAS says that multiplication comes before addition.

The x is a placeholder for a value. In this case, it is -7 as we go from f(x) to f(-7). All we've done is replace x with -7

f(x) = 2*x+8
f(-7) = 2*(-7)+8 ... replace every x with -7
f(-7) = -14+8
f(-7) = -6

Answer: -6
User Quilby
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.